Physics Learning Based on Virtual Laboratory to Remediate Misconception in Fluid Material - Diani, Rahma; Latifah, Sri; Anggraeni, Yanda Meilya; Fujiani, Dwi (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2018)
An understanding of concepts is very necessary in physics learning. It has been confirmed that often students have different understanding of scientific concepts, this term is what commonly called Misconception. Misconception is a problem that must be addressed immediately because misconception is one factor that causes students to experience difficulties in learning physics. This study aims to determine the effect of physics learning with the PDEODE model (predict-discuss-explain-observe-discuss-explain) assisted by virtual laboratory in the form of PhET simulation in remediating students’ misconceptions in the fluid material. This type of research is a Pre-Experimental One Group Pretest-Posttest design. The samples of this study were eleventh-grade science students of State Senior High School in Gadingrejo District, Lampung Province, taken through simple random sampling technique. The test used was in the form of a multi-tiered multiple-choice test of the four-tier diagnostic test with certainty response index (CRI) consisting of 20 items. The result of this study indicates that students' misconceptions decrease for all sub-concepts of fluid material. Based on the previously described statements, it can be concluded that physics learning based on virtual laboratory can remedy students' misconceptions, especially in fluid material.